2021
DOI: 10.3389/fchem.2020.619470
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Protein Structures in Lipid Bilayers; Small-Angle Neutron Scattering With Contrast-Matched Bicontinuous Cubic Phases

Abstract: This perspective describes advances in determining membrane protein structures in lipid bilayers using small-angle neutron scattering (SANS). Differentially labeled detergents with a homogeneous scattering length density facilitate contrast matching of detergent micelles; this has previously been used successfully to obtain the structures of membrane proteins. However, detergent micelles do not mimic the lipid bilayer environment of the cell membrane in vivo. Deuterated vesicles can be used to obtain the radiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Moreover, neutron scattering has the ability to detect the exact location of movable monomers and crosslinkers within the lyotropic liquid unit cell [ 191 , 192 , 193 ]. Leonie et al reported that the lipid LLC phases can be contrast-matched, and the scattering from encapsulated peptides and proteins can be isolated.…”
Section: Characterization Of Llc Phase/substrate Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, neutron scattering has the ability to detect the exact location of movable monomers and crosslinkers within the lyotropic liquid unit cell [ 191 , 192 , 193 ]. Leonie et al reported that the lipid LLC phases can be contrast-matched, and the scattering from encapsulated peptides and proteins can be isolated.…”
Section: Characterization Of Llc Phase/substrate Interfacementioning
confidence: 99%
“…Leonie et al reported that the lipid LLC phases can be contrast-matched, and the scattering from encapsulated peptides and proteins can be isolated. This enables them to better understand the location of the desired molecules during LLC structure evolution and phase transition [ 191 , 192 ]. Since the locations of monomers and crosslinkers during polymerization directly determine the pore structure of the as-synthesized LLC-templated materials, and the locations of these molecules could be very different at LLC/substrate interface, contrast matching the deuterated amphiphile molecules with solvents (a mixture of d-solvent and h-solvent) makes it possible to better detect and control the interface structures.…”
Section: Characterization Of Llc Phase/substrate Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…While liposomes are spherical, bicelles are flat discs with a rim of detergent (Dürr et al, 2013). Such nano-membranes are important tools to study the functions and properties of membrane proteins, as information can be extracted using different techniques, such as X-ray crystallography (Murugova et al, 2022; Ujwal & Bowie, 2011), cryo-EM (Wang & Sigworth, 2010; Yao et al, 2020), small-angle X-ray and neutron scattering (Conn et al, 2020; Dos Santos Morais et al, 2017), atomic force microscopy (Borrell et al, 2015; Sebinelli et al, 2019), and X-ray diffraction (Ruskamo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to high-resolution techniques, small-angle neutron scattering (SANS) is unique in providing insights into the structure of biomolecules in solution and at physiological temperatures. SANS bears great potential for advancing structural biology , and drug design. , However, in the case of membrane proteins, special attention should be paid to the detergent’s nontrivial contributions to the scattering data . The latter may arise from detergent interacting with the protein itself and from free detergent micelles present in the buffer solution.…”
Section: Introductionmentioning
confidence: 99%